2019
DOI: 10.1177/0954407019861241
|View full text |Cite
|
Sign up to set email alerts
|

A novel method to improve vehicle energy efficiency: Minimization of tire power loss

Abstract: The importance of energy efficiency, as one of the most crucial issues in automotive industry, has grown more rapidly considering the global energy crisis and climate change in recent years. This paper aims to introduce a method to increase the powertrain efficiency based on the minimization of tire power loss. Slip resistance is taken into account as well as rolling resistance to yield the modified tire resistance considered in this study. It is shown that the general optimal control problem can be reduced to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…(18) in backward simulations, where vehicle speed and acceleration are assumed to be known a priori, an appropriate inverse tire model should be used in which the tire slip is provided for a specific tractive force under determined conditions. A polynomial inverse tire model is provided by Sina et al [23], in which the coefficients are characterised as a function of performance parameters. Interested readers may refer to that paper for further details.…”
Section: Modified Vehicle Longitudinal Modelmentioning
confidence: 99%
“…(18) in backward simulations, where vehicle speed and acceleration are assumed to be known a priori, an appropriate inverse tire model should be used in which the tire slip is provided for a specific tractive force under determined conditions. A polynomial inverse tire model is provided by Sina et al [23], in which the coefficients are characterised as a function of performance parameters. Interested readers may refer to that paper for further details.…”
Section: Modified Vehicle Longitudinal Modelmentioning
confidence: 99%
“…Moreover, air resistance w P was considered as non-production resistance force, which can be reduced by a rational choice of the vehicle aerodynamic parameters. Since a decrease in non-productive energy costs contributes to an increase of capacity that can be used for vehicle acceleration (improving acceleration dynamics), a number of authors [6] suggested taking the power spent to accelerate the car as useful work.…”
Section: Analysis Of Publicationsmentioning
confidence: 99%
“…1,5,6 In spite of its simple design and implementability, CDCS strategy does not end in the optimal fuel consumption, which is regarded as a crucial shortcoming especially owing to progressively strict legislation on the vehicles' energy efficiency. [7][8][9][10] Utilizing the optimization based approaches would overcome such shortcoming by guarantying the optimality of fuel consumption through a driving cycle.…”
Section: Literature Reviewmentioning
confidence: 99%